The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1002/1521-4087(200009)25:4<186::aid-prep186>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Bond Between Stabilizers and HTPB Binders in Propellants

Abstract: The character of the chemical bond between stabilizers and isocyanates used to cure the HTPB binder was determined. The aim was to explain, why it is not possible to extract some stabilizers from the binder of rocket motors. Investigations were performed by 1H‐NMR‐spectroscopy on various combinations of stabilizers and isocyanates used to cure HTPB. It was demonstrated that stabilizes of some type can be attached to the polymeric network via a reaction with the di‐isocyanate. Criteria to evaluate the possibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The specifics of each test are detailed below. While it would have been beneficial to also determine the extent of anti-oxidant depletion on ageing, it has been demonstrated in the past that the two anti-oxidants employed in this propellant formulation are chemically bound into the cross-linked polybutadiene binder matrix and cannot be extracted for meaningful quantitative analysis [4].…”
Section: Methodsmentioning
confidence: 99%
“…The specifics of each test are detailed below. While it would have been beneficial to also determine the extent of anti-oxidant depletion on ageing, it has been demonstrated in the past that the two anti-oxidants employed in this propellant formulation are chemically bound into the cross-linked polybutadiene binder matrix and cannot be extracted for meaningful quantitative analysis [4].…”
Section: Methodsmentioning
confidence: 99%
“…2) indicated that the well-known yellowing of hindered phenol antioxidants (Vulic et al, 2002), even in the absence of oxygen (Bangee et al, 1995), may be related to the apparent change in HTPB reactivity, which was observed independently of the oxygen partial pressure. In fact, some studies (Celina et al, 2006;Désilets and Côté, 2006;Shanina, Zaikov and Mukmeneva, 1996) have demonstrated that quinone derivatives from hindered phenol antioxidants react quite readily with isocyanates and graphitize into HTPB backbone. Based on this literature evidence, our results indicate that the apparent increase of the HTPB/IPDI binder reactivity is due to a side-reaction between BHT quinone derivatives and IPDI.…”
Section: Resultsmentioning
confidence: 99%
“…Curing Agents or Crosslinkers: TDI is selected as crosslinking agent. Its purity is greater than 98% and the isomer ratio is 35/65 [4].…”
Section: B Solid Propellant Ingredients Bindersmentioning
confidence: 99%